Early outcomes and safety of outpatient (surgery center) vs inpatient based L5-S1 Anterior Lumbar Interbody Fusion. (March 2020) - Snowden, Ryan; Fischer, Dylan; Kraemer, Paul
Highlights: 62 consecutive patients underwent ALIF at a single site ASC and inpatient hospital. There were 8 total complications, none vascular related. Both groups showed improvement in outcome scores postoperatively. Our consecutive series demonstrates ALIF can be done safely in outpatient settings. Abstract: We seek to determine the outcomes of patients undergoing outpatient-based ALIF compared to a consecutive series of inpatient based ALIF performed during the same time period. 58 consecutive patients at a single outpatient surgery center underwent ALIF from June 2015 - August 2017 and 79 ALIF's were performed at 2 Inpatient hospitals. Electronic medical records were reviewed for perioperative and postoperative complications as well as secondary interventions. 62 patients met inclusion criteria (29 Outpatient, 33 Inpatient). The inpatient group was significantly older (44 vs 51; p = 0.01). There were 8 postoperative complications. There was no difference in secondary interventions; 28 patients underwent a total of 36 interventions postoperatively for pain. Secondary interventions were performed at an average of 128(outpatient) and 158(inpatient) days (p = 0.55). There was no difference in outcome scores between the inpatient/outpatient groups at any time. Patients receiving a secondary intervention showed no significant improvement in Back VAS scores but, demonstrated a strong trend (p = 0.06) towards leg pain improvement. Patients who did not undergo secondary intervention had significant improvement in both Back and Leg VAS scores at all time points (p < 0.05). Outpatient ALIF is a safe and reproducible procedure with complication rates consistent with or lower than published rates. Patients outcome scores were no different in the inpatient versus outpatient group. Interestingly, there was a high number of secondary interventions performed in both groups. Patients undergoing a secondary procedure did not get statistically significant improvement in Back VAS but, demonstrated a strong trend in Leg VAS patient reported outcome scores.